2016
DOI: 10.1021/acs.jmedchem.6b01092
|View full text |Cite
|
Sign up to set email alerts
|

Hit-to-Lead Optimization of Mouse Trace Amine Associated Receptor 1 (mTAAR1) Agonists with a Diphenylmethane-Scaffold: Design, Synthesis, and Biological Study

Abstract: The trace amine-associated receptor 1 (TAAR1) is a G-protein-coupled receptors (GPCR) potently activated by a variety of molecules besides trace amines (TAs), including thyroid hormone-derivatives like 3-iodothyronamine (T1AM), catechol-O-methyltransferase products like 3-methoxytyramine, and amphetamine-related compounds. Accordingly, TAAR1 is considered a promising target for medicinal development. To gain more insights into TAAR1 physiological functions and validation of its therapeutic potential, we recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…However, due to the structural similarity with their prototypes, most of these small molecules continued to be affected by an impaired selectivity profile towards the TAAR1 receptor with respect to other, highly related G-protein-coupled receptors (GPCRs) (monoaminergic systems) [13]. By chemical manipulation of T 1 AM, Chiellini et al developed a class of halogen-free diphenylmethane derivatives, which displayed both in vitro and in vivo efficacy [14,15]. Later analogues showed a potency similar or even superior to that of their prototypes as TAAR1 agonists; however, these molecules shared with T 1 AM some non-TAAR1-mediated functional effects (e.g., stimulation of hepatic gluconeogenesis), which require further investigation for an adequate evaluation of the selectivity issue [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the structural similarity with their prototypes, most of these small molecules continued to be affected by an impaired selectivity profile towards the TAAR1 receptor with respect to other, highly related G-protein-coupled receptors (GPCRs) (monoaminergic systems) [13]. By chemical manipulation of T 1 AM, Chiellini et al developed a class of halogen-free diphenylmethane derivatives, which displayed both in vitro and in vivo efficacy [14,15]. Later analogues showed a potency similar or even superior to that of their prototypes as TAAR1 agonists; however, these molecules shared with T 1 AM some non-TAAR1-mediated functional effects (e.g., stimulation of hepatic gluconeogenesis), which require further investigation for an adequate evaluation of the selectivity issue [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Collectively, these findings indicated that T1AM might represent a valuable tool to investigate the physiological role and pharmacological potentials of TAAR1, as well as a good starting point to advance development of new targets for potential therapeutic interventions in a wide array of pathological processes, including metabolic, endocrine, and neurological disorders. In this context, with the aim to ameliorate the number of selective TAAR1 agonists, Chiellini et al (2015 , 2016 ), recently developed a novel class of halogen free biaryl-methane thyronamine analogs, namely SG compounds, synthetically more accessible than traditional thyronamines. Following a multidisciplinary approach, they identified two compounds, namely SG-1 and SG-2 ( Figure 1 ), that appeared to be equipotent to endogenous thyronamines (i.e., T0AM and T1AM, respectively), providing additional tools for studying the physiological roles of TAAR1 receptor using in vitro and/or in vivo models.…”
Section: Introductionmentioning
confidence: 99%
“…Within this new series of T1AM analogues, the benzylated congeners revealed to possess a better TAAR1 affinity [101,102]. Later, our group discovered a novel class of promising thyronamine-like analogs [103,104]. Starting from T1AM, selected structural modifications, including the substitution of the oxygen bridging the two aryl rings with a methylene spacer, replacement of the ethylamine side chain with an aminoethoxy group, replacement of the 3-iodo substituent with hydrogen or methyl group, and bioisosteric transformation of the 4 -OH substituent with 4 -NH 2 , were carried out aiming to (i) obtain more synthetically accessible compounds, and (ii) improve pharmacokinetic properties.…”
Section: Novel 3-iodothyronamine Derivativesmentioning
confidence: 99%